A Suggested Instructional Guide for Patients with Vagus Nerve Inflammation (Journal of the College of Education for Women, 2025)
Diseases are one of the major challenges facing all societies, which must be treated and united for the development of these societies. Medical clinics and counseling centers must deal carefully with patients, especially those with complex diseases such as vagus nerve inflammation. The difficulty of bearing the costs of medications and the scarcity or high cost of some of the treatments and medications necessary for these diseases. Many images that translate to the psychological and social problems of individuals, which have become clear and numerous, in addition to that, the scarcity of specialist doctors in neurological diseases and the difficulty of reaching them at any time or any place, where neurologist clinics are filled with patients. The researchers found it necessary to develop a guide that helps the patient recover with simple and clear steps. It included 10 lists, each list having specific content: Definitions and meanings of the guide's terms. Goals, visions, message, and philosophy of the guide and the need for it. How the guide is applied. Definition of the disease. Diagnosis of vagus nerve inflammation. Clinical laboratory examination procedures. Clinical (laboratory) examination: Head-up tilting table. Treatment of vagus nerve inflammation. Things the patient must adhere to. Things the patient must avoid. It obtained the approval of (20) experts in the field of guidance, and was applied to (25) patients with vagus nerve inflammation and their (36) companions at Al-Tariq Clinic Hay Al-Jamaa in Baghdad. The researchers put forward some recommendations and suggestions, including the preparation of a guide for diseases of the peripheral nervous system.